Frequency stabilization using BESS of EV : a statistical analysis - Lim, Jonathan Wei Zheng. (2013)
The project is an investigation on the use of electric vehicle (EV) batteries to stabilize network frequency of power systems. Using MatLab Simulink, a model has been developed to study the frequency response to a step load change. An attempt is made to produce a response to stabilize the system with respect to the step load change. The electric vehicle used in this project is the Renault Fluence EV. The lithium ion battery inside this vehicle’s design is also used as a component of study to explore the possibilities of network stabilization based in Singapore.